HUBUNGAN POWER OTOT LENGAN DENGAN KEMAMPUAN SMASH PERMAINAN BULUTANGKIS PADA SISWA KELAS VII SMP - Waly, Silvia Agnesi; Karim, Karim (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This research is motivated by the students' learning outcomes, which still show many deficiencies in performing a good smash during practice and matches. The objective of this research is to determine the relationship between arm muscle power and smash ability in badminton among 7th-grade students at SMP Negeri 40 Buton. The research approach used is a quantitative approach. This research falls under the category of descriptive research, using a correlational method to determine the relationship between arm muscle power and smash ability in badminton. The instruments used in this research are the Arm Muscle Power Test to measure the components of arm muscle power and the Badminton Smash Stroke Ability. The results and discussion of the research show that there is a significant relationship between arm muscle power and smash ability in badminton, with a correlation coefficient of rxy = 0.65 > the table value of r = 0.334. The coefficient of determination, r2 = 0.652 = 0.42 or 42%, indicates that arm muscle power contributes 42% to the smash ability in badminton, while 58% is influenced by other factors such as strength, speed, accuracy, balance, flexibility, and coordination..